Mammographic density and prognosis in primary breast cancer patients. (October 2021) - Heindl, Felix; Fasching, Peter A.; Hein, Alexander; Hack, Carolin C.; Heusinger, Katharina; Gass, Paul; Pöschke, Patrik; Stübs, Frederik A.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias W.; et al.
Abstract: Purpose: Mammographic density (MD) is one of the strongest risk factors for breast cancer (BC). However, the influence of MD on the BC prognosis is unclear. The objective of this study was therefore to investigate whether percentage MD (PMD) is associated with a difference in disease-free or overall survival in primary BC patients. Methods: A total of 2525 patients with primary, metastasis-free BC were followed up retrospectively for this analysis. For all patients, PMD was evaluated by two readers using a semi-automated method. The association between PMD and prognosis was evaluated using Cox regression models with disease-free survival (DFS) and overall survival (OS) as the outcome, and the following adjustments: age at diagnosis, year of diagnosis, body mass index, tumor stage, grading, lymph node status, hormone receptor and HER2 status. Results: After median observation periods of 9.5 and 10.0 years, no influence of PMD on DFS ( p  = 0.46, likelihood ratio test (LRT)) or OS ( p  = 0.22, LRT), respectively, was found. In the initial unadjusted analysis higher PMD was associated with longer DFS and OS. The effect of PMD on DFS and OS disappeared after adjustment for age and was caused by the underlying age effect. Conclusions: Although MD is one of the strongest independent risk factors for BC, in our collective PMD is not associated with disease-free and overall survival in patients with BC. Highlights: Mammographic density (MD) is one of the strongest risk factors for breast cancer (BC). Results from a large BC cohort on the impact of percentage MD (PMD) on prognosis. No association between PMD with disease-free and overall survival was found. Risk stratification based on PMD seems not feasible for clinical routine.